2002
DOI: 10.1063/1.1499735
|View full text |Cite
|
Sign up to set email alerts
|

Maximization of the open circuit voltage for hydrogenated amorphous silicon n–i–p solar cells by incorporation of protocrystalline silicon p-type layers

Abstract: In studies of hydrogenated amorphous silicon (a-Si:H) n-i-p solar cells fabricated by rf plasma-enhanced chemical vapor deposition ͑PECVD͒, we have found that the maximum open circuit voltage (V oc) is obtained by incorporating p-type doped Si:H layers that are protocrystalline in nature. Specifically, these optimum p layers are prepared by PECVD in the a-Si:H growth regime using the maximum hydrogen-to-silane flow ratio possible without crossing the thickness-dependent transition into the mixed-phase (amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…The fact that no such resonance is found even when Raman intensities suggest a complete amorphous structure remains another challenge for future investigations. Could different medium range order in so called "protocrystalline" material [43] with different environment of defects be a reason for this?…”
Section: Discussionmentioning
confidence: 98%
“…The fact that no such resonance is found even when Raman intensities suggest a complete amorphous structure remains another challenge for future investigations. Could different medium range order in so called "protocrystalline" material [43] with different environment of defects be a reason for this?…”
Section: Discussionmentioning
confidence: 98%
“…For growing a nc-Si:H player, we used a high hydrogen dilution (H 2 /SiH 4 = 166) and a high gas pressure of 2 Torr, as well as a high RF power density of 0.7 W/cm 2 at a low substrate temperature of 70°C (sample A). To enhance the formation of nanocrystalline nucleation sites for the p-layer deposition in the n-i-p type a-Si:H solar cells, we performed a H 2 -plasma treatment for the underlying i-layer surface (sample B), as has been employed in other laboratories [7]. In contrast, for suppressing the formation of nanostructures in the p-layer, we increased the ion-bombardments on the growing surface by using a larger RF power density of 1.1 W/cm 2 , while keeping the hydrogen dilution unchanged (sample C).…”
Section: Methodsmentioning
confidence: 99%
“…Rath et al reported that using a truly lc-Si:H p-layer in a-Si:H p-i-n cells could induce a disastrous effect on the V oc and fill factor (FF), when no buffer between p-and i-layer was used [6]. In a recent report, Koval et al argued that 10-20 nm thick p-layers prepared on i-layers may be amorphous even at hydrogen dilution values as high as 200, due to a possible barrier to microcrystal nucleation on an amorphous i-layer surface [7]. Moreover, the authors proposed that the maximum V oc is obtained by incorporating p-type doped Si:H layers that are protocrystalline in nature, and even relatively low, substrate-induced microcrystalline fractions in the p-layer are detrimental.…”
Section: Introductionmentioning
confidence: 97%
“…In order to reduce the absorption loss in the nc-Si:H emitter layers, it is necessary to minimize the thickness of the amorphous incubation phase. Furthermore, Koval et al [5] argued that 10-20 nm thick p-layers prepared on i-layers may be amorphous even at high hydrogen dilution because there is a possible barrier to nucleation on an amorphous layer surface. However, other groups [6,7] found that films can be highly crystallized at high hydrogen diluton even when the film thickness is ∼10 nm.…”
Section: Introductionmentioning
confidence: 98%